Two graves - Preston, Douglas J. (Preston, Douglas J. Pendergast novel., 2012)
Special Agent Pendergast assists NYPD Lieutenant D'Agosta in the investigation of a number of killings that ultimately prove to be messages from his wife's kidnappers.